2020
DOI: 10.3382/ps/pez568
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of a QX-like avian infectious bronchitis virus isolated in China

Abstract: Avian infectious bronchitis is a serious and highly contagious disease caused by infectious bronchitis virus (IBV). We isolated a highly virulent IBV strain (CK/CH/JS/TAHY) from kidneys of diseased chickens. Phylogenetic analysis based on the S1 gene revealed that CK/CH/JS/TAHY clustered with the QX-like type. The S1 gene has 1,620 nucleotides and encoded a polypeptide of 540 amino acids with typical coronavirus cleavage recognition sites of HRRR. About 1-day-old specific pathogen-free White Leghorn chickens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Coincidently, no obvious gross lesions were observed and viral antigens were not detected by IHC in the proventriculi of chickens infected with the isolate I0305/19, although the isolate I0305/19 can replicate efficiently in the proventriculi by viral titration using 9-day-old SPF chicken eggs. In addition, only very mild respiratory signs were observed in both the commercial broilers and the SPF chickens infected with isolate I0305/19; however, other reports demonstrated that the GI-19 viruses could induce obvious respiratory signs (Liu and Kong et al, 2004;Benyeda et al, 2009;Choi et al, 2009;Zhong et al, 2016;Khanh et al, 2018;Xu et al, 2018;Li et al, 2019;Ren et al, 2019a;Yan et al, 2019). The isolate I0305/19 can replicate efficiently in both the trachea and lungs in the infected SPF chickens, which was demonstrated by viral titration in SPF chicken eggs and viral antigen detection by IHC.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Coincidently, no obvious gross lesions were observed and viral antigens were not detected by IHC in the proventriculi of chickens infected with the isolate I0305/19, although the isolate I0305/19 can replicate efficiently in the proventriculi by viral titration using 9-day-old SPF chicken eggs. In addition, only very mild respiratory signs were observed in both the commercial broilers and the SPF chickens infected with isolate I0305/19; however, other reports demonstrated that the GI-19 viruses could induce obvious respiratory signs (Liu and Kong et al, 2004;Benyeda et al, 2009;Choi et al, 2009;Zhong et al, 2016;Khanh et al, 2018;Xu et al, 2018;Li et al, 2019;Ren et al, 2019a;Yan et al, 2019). The isolate I0305/19 can replicate efficiently in both the trachea and lungs in the infected SPF chickens, which was demonstrated by viral titration in SPF chicken eggs and viral antigen detection by IHC.…”
Section: Discussionmentioning
confidence: 94%
“…GI-19 field strains showed different levels of virulence to SPF chickens in experimental infections. Some strains isolated in China were nonpathogenic to SPF chicken (Yan et al, 2017), while others showed low to high pathogenicity to SPF chickens, with morbidity ranging from 40 % to 100 % and mortality ranging between 10 % and 80 % (Table 1) (Liu and Kong, 2004;Zhong et al, 2016;Yan et al, 2017;Xu et al, 2018;Li et al, 2019;Ren et al, 2019aRen et al, ,2019b. The GI-19 virus strain isolated in Malaysia was also highly virulent to SPF chickens with 100 % morbidity and 41.3 % mortality (Khanh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One IBV strain, H120 strain, usually needs to be identified from other strains for immunoprophylaxis and vaccine production, for example, NNA strain. Both of them are composed of structural and nonstructural proteins [ 2 , 3 ]. The spike (S) glycoprotein is one of the major structural proteins which can be post-translationally cleaved into S1 and S2 subunits [ 4 ].…”
Section: Introductionmentioning
confidence: 99%